Adsorption and Thermal Evolution of the Carbonyl-functionalized Ionic Liquid [5-oxo-C6C1Im][NTf2] on Pt(111): A Combined IRAS, STM, and DFT Study - Bühlmeyer, Hanna; Knörr, Lukas; Steffen, Julien; Eschenbacher, Roman; Hauner, Jonas; Görling, Andreas; Libuda, Jörg (Chemistry - A European Journal, 2024)
The coating of heterogeneous catalysts with ionic liquids enables precise tuning of catalytic activity and selectivity. Recently, the fundamentals of solid catalysts with ionic liquid layers have been extensively studied. So far, investigations have focused on simple ILs without specialized functional groups. In our current work, we aim to involve functionalized ILs to take advantage of the interactions between these functional groups, the catalyst, and the reactants. In this study, we investigated the interaction, and thermal stability of the carbonyl-functionalized IL [5-oxo-C6C1Im][NTf2] on Pt(111) by infrared reflection absorption spectroscopy and scanning tunneling microscopy. In addition, we performed density functional theory calculations to support our interpretation. At 200 K and low coverage, the carbonyl group of the [5-oxo-C6C1Im]+ cation is oriented parallel to the Pt(111) surface. With increasing coverage, the alkyl chain detaches from the surface and orients towards the vacuum. The [NTf2]− anion adsorbs parallel to the surface via the oxygen atoms of the SO2 groups. At higher coverage, at least one of the SO2 groups completely detaches from the surface. Upon heating to 250 K, we observe decomposition and partial desorption of [5-oxo-C6C1Im][NTf2], with further decomposition and desorption occurring between 350 and 400 K.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Infrared reflection absorption spectroscopy; Ionic liquids; Scanning tunneling microscopy; Pt(111); SCILL

CuTe chains on Cu(111) by deposition of one-third of a monolayer of Te: Atomic and electronic structure - Kißlinger, Tilman; Raabgrund, Andreas; Geldiyev, Begmuhammet; Ammon, Maximilian Michael; Rieger, Janek; Hauner, Jonas; Hammer, Lutz; Fauster, Thomas; Schneider, M. Alexander (Physical Review B, 2020)
The surface atomic and electronic structure after deposition of one-third of a monolayer Te on Cu(111) was determined using a combination of low-energy electron diffraction (LEED), scanning tunneling microscopy and spectroscopy (STM/STS), angle-resolved single and two-photon photoelectron spectroscopy (ARPES /AR-2PPE), and density functional theory (DFT) calculations. Contrary to the current state in literature, Te does not create a two-dimensional surface alloy but forms Cu2Te2 adsorbate chains in a (2√3×√3)R30∘ superstructure. We establish this by a high-precision LEED-IV structural analysis with Pendry R factor of R=0.099 and corroborating DFT and STM results. The electronic structure of the surface phase is dominated by an anisotropic downward dispersing state at the Fermi energy EF and a more isotropic upward dispersing unoccupied state at E−EF=+1.43eV . Both states coexist with bulk states of the projected band structure, and are therefore surface resonance

Epitaxial inorganic metal-halide perovskite films with controlled surface terminations - Rieger, Janek; Kißlinger, Tilman; Raabgrund, Andreas; Hauner, Jonas; Niesner, Daniel; Schneider, M. Alexander; Fauster, Thomas (Physical Review Materials, 2023)
Metal-halide perovskite (MHP) thin films for next-generation solar cells are typically fabricated by wet-chemical synthesis in which surface properties such as the orientation of surface facets and their termination cannot be controlled. MHP device efficiencies depend critically on those surface properties. We demonstrate the epitaxial growth of several nanometer thick purely (001)-orientated films of CsPbBr3 and CsSnBr 3 MHPs on Au(001) by molecular beam epitaxy. The epitaxial films are in a cubic phase aligned with the substrate. Their surfaces are singly terminated and can be modified for the first time. While the CsBr and PbBr2 surface terminations differ in terms of their atomic structure and defect content, the films are intrinsic semiconductors irrespective of the termination. The work function of the PbBr2-terminated surface is increased by 0.7eV, which has drastic implications for the level alignment at MHP interface

Mechanistic Study of Ethanol Decomposition on Co3O4(111) and Pd/Co3O4(111) Model Catalysts - Reindl, Simone; Škvára, Jan; Hauner, Jonas; Simanenko, Alexander; Kastenmeier, Maximilian; Ronovský, Michal; Skála, Tomáš; Tsud, Nataliya; Kettner, Miroslav; Mehl, Sascha; Vorochta, Michael; Šmíd, Břetislav; et al. (ChemCatChem, 2024)
In many advanced catalytic materials, different functionalities are coupled through spillover of active species across heterogeneous interfaces. In the present work, we consider the coupling of a C─C bond cleavage functionality of palladium with the self-cleaning functionality of reducible Co3O4. On the model catalyst Pd/Co3O4(111)/Ir(100), we probed the interplay of the two functionalities for the selective decomposition of ethanol. In a systematic study, we compared the decomposition mechanisms of ethanol on Co3O4(111)/Ir(100) and Pd/Co3O4(111)/Ir(100) model catalysts using a variety of analytical techniques including synchrotron radiation photoelectron spectroscopy (SRPES), resonant photoemission spectroscopy (RPES), temperature programmed desorption (TPD), and near ambient pressure X-ray photoelectron spectroscopy (NAP-XPS). We found that ethanol decomposes via an ethoxy intermediate yielding acetaldehyde on Co3O4(111)/Ir(100). Remarkably, the spillover of ethanol/ethoxy species on Pd/Co3O4(111)/Ir(100) results in the selective formation of methane, hydrogen, and CO. Additionally, we observed CO2 resulting from the oxidative removal of carbonaceous deposits on Pd nanoparticles via spillover of active oxygen species released by Co3O4(111)/Ir(100) at higher temperatures. The onset of product formation and the product spectrum on both Co3O4(111)/Ir(100) and Pd/Co3O4(111)/Ir(100) depend strongly on the oxidation state of Co3O4. Complete removal of lattice oxygen from Co3O4(111) results in the deposition of large amounts of carbon.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Cobalt oxide; Ethanol; Nanoparticles; Palladium; Spillover

Structure Formation in an Ionic Liquid Wetting Layer: A Combined STM, IRAS, DFT and MD Study of [C2C1Im][OTf] on Au(111) - Bühlmeyer, Hanna; Hauner, Jonas; Eschenbacher, Roman; Steffen, Julien; Trzeciak, Simon; Taccardi, Nicola; Görling, Andreas; Zahn, Dirk; Wasserscheid, Peter; Libuda, Jörg (Chemistry - A European Journal, 2023)
In a solid catalyst with ionic liquid layer (SCILL), ionic liquid (IL) coatings are used to improve the selectivity of noble metal catalysts. To understand the origins of this selectivity control, we performed model studies by surface science methods in ultrahigh vacuum (UHV). We investigated the growth and thermal stability of ultrathin IL films by infrared reflection absorption spectroscopy (IRAS). We combined these experiments with scanning tunneling microscopy (STM) to obtain information on the orientation of the ions, the interactions with the surface, the intermolecular interactions, and the structure formation. Additionally, we performed DFT calculations and molecular dynamics (MD) simulations to interpret the experimental data. We studied the IL 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [C2C1Im][OTf] on Au(111) surfaces. We observe a weakly bound multilayer of [C2C1Im][OTf], which is stable up to 390 K, while the monolayer desorbs at ∼450 K. [C2C1Im][OTf] preferentially adsorbs at the step edges and elbows of the herringbone reconstruction of Au(111). The anion adsorbs via the SO3 group with the molecular axis perpendicular to the surface. At low coverage, the [C2C1Im][OTf] crystallizes in a glass-like 2D phase with short-range order. At higher coverage, we observe a phase transition to a 6-membered ring structure with long-range order.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Au(111); SCILL; infrared reflection absorption spectroscopy; ionic liquids; scanning tunneling microscopy

Surface carrier dynamics and diffusion in inorganic metal-halide perovskite films - Rieger, Janek; Hauner, Jonas; Niesner, Daniel; Fauster, Thomas (Physical Review B, 2023)
Carrier dynamics in metal-halide perovskites, in particular diffusion, has typically been investigated on micrometre-length scales and above. However, surfaces and interfaces modify the carrier dynamics, e.g., by interface band bending and recombination. To investigate the carrier dynamics and diffusion at the surface, we use time-resolved photoelectron spectroscopy which is sensitive to the photoexcited carriers in the topmost few nm of the material. We extract electron mobilities in well-ordered CsPbBr 3 (001) and CsSnBr3(001) films at room temperature of 31±6 and 13±1cm2V−1s−1, respectively. The mobility in CsPbBr3(001) increases to 200±8cm2V−1s−1 at 90 K, indicating strong electron-phonon coupling for electrons at the conduction band minimum. Temperature-dependent photoemission experiments find different phonon coupling mechanisms for high-energetic electrons and holes at the valence band maximum and in the main valence band

Surface Chemistry of a [C2C1Im][OTf] (Sub)Wetting Layer on Pt(111): A Combined XPS, IRAS, and STM Study - Bühlmeyer, Hanna; Talwar, Timo; Eschenbacher, Roman; Barreto, Jade; Hauner, Jonas; Knörr, Lukas; Steinrück, Hans-Peter; Maier, Florian; Libuda, Jörg (ACS Applied Materials and Interfaces, 2024)
The concept of a solid catalyst with an ionic liquid layer (SCILL) is a promising approach to improve the selectivity of noble metal catalysts in heterogeneous reactions. In order to understand the origins of this selectivity control, we investigated the growth and thermal stability of ultrathin 1-ethyl-3-methylimidazolium trifluormethanesulfonate [C2C1Im][OTf] films on Pt(111) by infrared reflection absorption spectroscopy (IRAS) and X-ray photoelectron spectroscopy (XPS) in time-resolved and temperature-programmed experiments. We combined these spectroscopy experiments with scanning tunneling microscopy (STM) to obtain detailed insights into the orientation and adsorption geometry of the ions in the first IL layer. Furthermore, we propose a mechanism for the thermal evolution of [C2C1Im][OTf] on Pt(111). We observe an intact IL layer on the surface at temperatures below 200 K. Adsorbed [C2C1Im][OTf] forms islands, which are evenly distributed over the surface. The [OTf]− anion adsorbs via the SO3 group, with the molecular axis perpendicular to the surface. Anions and cations are arranged next to each other, alternating on the Pt(111) surface. Upon heating to 250 K, we observe changes in geometry and structural distribution. Whereas at low temperature, the ions are arranged alternately for electrostatic reasons, this driving force is no longer decisive at 250 K. Here, a phase separation of two different species is discernible in STM. We propose that this effect is due to a surface reaction, which changes the charge of the adsorbates. We assume that the IL starts to decompose at around 250 K, and thus, pristine IL and decomposition products coexist on the surface. Also, IRAS and XPS show indication of IL decomposition. Further heating leads to increased IL decomposition. The reaction products associated with the anions are volatile and leave the surface. In contrast, the cation fragments remain on the surface up to temperatures above 420 K.
CRIS-Team Scopus Importer:2024-05-10
Keywords: infrared reflection absorption spectroscopy; ionic liquids; Pt(111); scanning tunneling microscopy; SCILL; X-ray photoelectron spectroscopy